PREPARASI DAN KARAKTERISASI KOMPOSIT KROMIUM OKSIDA-MONTMORILLONIT - Sutha Negara, I M.; Wijaya, Karna; Sugiharto, Eko (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 2 Juli 2008, 2012)
The objectives of this research were to prepare montmorillonite and of chromium oxide-montmorillonite composite by intercalation of oxide of chrom into the silicates interlayer of montmorillonite, and to characterize some of their physical and chemical properties. The characterization indicated that the basal spacing d001 was increased from 14,11 in montmorillonit to 15,55 in chromium oxide-montmorillonite; specific surface area was increased from 69,71 m2/g to 240,40 m2/g; total pore volume was also increased from 0,05 mL/g to 0,128 mL/g; and chrom content also increased from 0,007% (w/w) to 17,16 % (w/w).
Keywords: montmorillonite clay, intercalation, chromium oxide-montmorillonite